Australian Rainforests : Islands of Green in a Land of Fire. - Bowman, D. M. J. S. (Cambridge : Cambridge University Press, 2000)
This book is a comprehensive overview of the diverse literature that attempts to solve the puzzle of the archipelago of rainforest habitats in Australia. It is essential reading for all ecologists, foresters, conservation biologists, and others interested in the biogeography and ecology of Australian rainforests.
Intro -- Contents -- Preface -- Introduction -- What is Australian rainforest? -- The sclerophyll problem -- The edaphic theory I. The control of rainforest by soil phosphorus -- The edaphic theory II. Soil types, drainage, and fertility -- The climate theory I. Water stress -- The climate theory II. Light and temperature -- The fire theory I. Field evidence -- The fire theory II. Fire, nutrient cycling, and topography -- The fire theory III. Fire frequency, succession, and ecological drift -- The fire theory IV. Aboriginal landscape burning -- The fire theory V. Aridity and the evolution of flammable forests -- The fire theory VI. Fire management and rainforest conservation -- Summary -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Rain forest ecology--Australia.; Electronic books